2021
DOI: 10.1007/s10989-021-10331-8
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Analysis of Inhibiting Papain-like Protease from SARS-CoV-2 by Using Plant-Derived Peptides

Abstract: SARS-CoV-2 is a corona virus that has been the cause for one of the deadliest pandemics of history, started since 2019. Suppressing the activity of the critical enzymes in the SARS-CoV-2 could potentially inhibit a vital step in viral life cycle. Papain-like protease (PLpro) could be regarded as a critical enzyme in viral replication of SARS-CoV-2. In this research, it was aimed to suppress the activity of PLpro enzyme by using potential plant-derived protease inhibitor peptides. For this purpose, 11 plant der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Some of the studies discussed in this review may contribute to the repurposing of drugs or current antiviral compounds (Chowdhury et al, 2020;Pant et al, 2020). Other reports may facilitate the discovery of novel anti-SARS-CoV-2 agents from food and other bioresources (Yu et al, 2021;Yathisha et al, 2022;Moradi et al, 2022), thereby adding value to such biomaterials. Potential SARS-CoV-2 inhibitory peptides have also been identified from many other novel bioresources, such as edible insects (Wong et al, 2020;Ong et al, 2021).…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some of the studies discussed in this review may contribute to the repurposing of drugs or current antiviral compounds (Chowdhury et al, 2020;Pant et al, 2020). Other reports may facilitate the discovery of novel anti-SARS-CoV-2 agents from food and other bioresources (Yu et al, 2021;Yathisha et al, 2022;Moradi et al, 2022), thereby adding value to such biomaterials. Potential SARS-CoV-2 inhibitory peptides have also been identified from many other novel bioresources, such as edible insects (Wong et al, 2020;Ong et al, 2021).…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%
“…Moradi and co-workers screened 11 plant-derived peptides from the literature that could potentially inhibit PL pro activity (Moradi et al, 2022). They found that the peptide VcTI from Veronica hederifolia provided effective molecular interactions at both the liable zinc site and the classic active site of PL pro .…”
Section: Peptide-pl Pro Interactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally suppressing the activity of the PLpro enzyme by using potential plant-derived protease inhibitor peptides has also been considered. (Moradi et al, 2022) have tested 11 plant-derived peptides selected from the literature that could potentially inhibit protease activity. Docking experiments suggest that VcTI from Veronica hederifolia provides effective molecular interactions at both the liable Zn site and the classic active site of PLpro.…”
Section: Searching For Natural Peptides Active Against Severe Acute R...mentioning
confidence: 99%